Week 6
-
Boolean Algebra = formal system of describing Boolean logical statements (functions) invented by Geoge Boole (1800’s)
-
Algebra = a set of elements (the carrier of the algebra), and operators defined on the carrier
-
Calculus = a method of reasoning by calculation with symbols...
The 7 Boolean Operators:
-
NOT: NOT X = 0 if X is 1, = 1 otherwise (X')
-
AND: X AND Y = 1 if X and Y are 1, = 0 otherwise (X*Y or X.Y)
-
NAND: X NAND Y = 0 if X & Y are 1, = 1 otherwise
-
OR: X OR Y = 0 if X & Y are 0, = 1 otherwise (X+Y)
-
NOR: X NOR Y = 1 if X & Y are 0, = 0 otherwise
-
XOR: X XOR Y = 0 if X & Y are the same, = 1 otherwise
-
XNOR: X XNOR Y = 1 if X & Y are the same, = 0 otherwise
INPUTS
|
BASIC OPERATORS
|
X
|
Y
|
X AND Y
|
X NAND Y
|
X OR Y
|
X NOR Y
|
X XOR Y
|
X XNOR Y
|
0
|
0
|
0
|
1
|
0
|
1
|
0
|
1
|
0
|
1
|
0
|
1
|
1
|
0
|
1
|
0
|
1
|
0
|
0
|
1
|
1
|
0
|
1
|
0
|
1
|
1
|
1
|
0
|
1
|
0
|
0
|
1
|
Analysing Boolean functions:
Method 1: Truth Tables
Given a function: F = (X OR (X AND Y)) OR (Y AND (Y OR (NOT Z)))
note: operator precedence is: NOT > AND > OR
Inputs
|
Intermediate computations...
|
Output
|
X
|
Y
|
Z
|
X AND Y
|
X OR (X AND Y)
|
NOT Z
|
Y OR (NOT Z)
|
Y AND (Y OR (NOT Z))
|
F
|
0
|
0
|
0
|
0
|
0
|
1
|
1
|
0
|
0
|
0
|
0
|
1
|
0
|
0
|
0
|
0
|
0
|
0
|
0
|
1
|
0
|
0
|
0
|
1
|
1
|
1
|
1
|
0
|
1
|
1
|
0
|
0
|
0
|
1
|
1
|
1
|
1
|
0
|
0
|
0
|
1
|
1
|
1
|
0
|
1
|
1
|
0
|
1
|
0
|
1
|
0
|
0
|
0
|
1
|
1
|
1
|
0
|
1
|
1
|
1
|
1
|
1
|
1
|
1
|
1
|
1
|
1
|
1
|
0
|
1
|
1
|
1
|
note: we can deduce that F = X OR Y
Method 2: Boolean algebra
Typical shorthand: * AND + OR ' NOT
F = (X OR (X AND Y)) OR (Y AND (Y OR (NOT Z)))
= (X + (X * Y)) + (Y * (Y + Z'))
F is a combination of: the logic operators (+, *, ') & operands (X, Y, Z)
Many operators (and functions) can be constructed from these basic ones:
-
X NAND Y = (X * Y)'
-
X NOR Y = (X + Y)'
-
X XOR Y = (X' * Y) + (X * Y')
eg: Evaluate: F = (X + (X * Y)) + (Y * (Y + Z')) when X = 1, Y = 0, Z = 1
= (1 + (1 * 0)) + (0 * (0 + 1'))
= (1 + 0) + (0 * (0 + 0))
= 1 + (0 * 0)
= 1 + 0
= 1
To simplify F we can use some laws:
-
Law 1: P * P = P
-
Law 2: P * (Q + R) = (P * Q) + (P * R)
-
Law 3: P + (P * Q) = P
F = (X + (X * Y)) + (Y * (Y + Z'))
= X + (Y * (Y + Z')) {using Law 3}
= X + ((Y * Y) + (Y * Z')) {using Law 2}
= X + (Y + (Y * Z')) {using Law 1}
= X + (Y) {using Law 2}
= X + Y
Share with your friends: |